(3BOGH GdUhajIs - (3eMeO Hf GdMSjf Hf eMeO Hf ehSi GdCROj GdSdej GdfjSGHhQj, CHh YHO GdQMef,J (B412 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe CHhYHOGdQMef GdSdej QMeI Gddg Ydjg GdMeO ddg GdPj Rjf ChdjGAg HBOGH GdXhGgQ hGdHhGWf s
(3BNQgG (B:s
(3hjchf PcQg hacQg JMJ eQGbHJg hGLJgGOg aj JWgjQ GdNdGFb ef bdHg hdGjTJZd HShGg adjaYd hGdSdGe Je s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B258s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B42s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdJUha hGdBOGH GdTQYjIs